2016
DOI: 10.1001/jamasurg.2016.2798
|View full text |Cite
|
Sign up to set email alerts
|

Standard vs Distal Roux-en-Y Gastric Bypass in Patients With Body Mass Index 50 to 60

Abstract: Clinicaltrials.gov Identifier: NCT00821197.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 47 publications
6
37
2
1
Order By: Relevance
“…Surveillance and Treatment of Dyslipidaemia after Bariatric Surgery: On average, serum total-cholesterol, LDL-cholesterol, HDL-cholesterol and triglycerides decline during the first 6 weeks after gastric bypass [66,73]. Several studies demonstrated that the LDL-cholesterol and triglyceride levels were reduced until 1 year and then stabilized in parallel with the period of maximum weight loss (1-2 years), while HDL-cholesterol increases from 6 weeks to 1-2 years above the baseline level [66,73].…”
Section: Management Of Co-morbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveillance and Treatment of Dyslipidaemia after Bariatric Surgery: On average, serum total-cholesterol, LDL-cholesterol, HDL-cholesterol and triglycerides decline during the first 6 weeks after gastric bypass [66,73]. Several studies demonstrated that the LDL-cholesterol and triglyceride levels were reduced until 1 year and then stabilized in parallel with the period of maximum weight loss (1-2 years), while HDL-cholesterol increases from 6 weeks to 1-2 years above the baseline level [66,73].…”
Section: Management Of Co-morbiditiesmentioning
confidence: 99%
“…Several studies demonstrated that the LDL-cholesterol and triglyceride levels were reduced until 1 year and then stabilized in parallel with the period of maximum weight loss (1-2 years), while HDL-cholesterol increases from 6 weeks to 1-2 years above the baseline level [66,73]. In general, the proportion of patients taking lipid-lowering drugs after bariatric surgery tends to reduce [74].…”
Section: Management Of Co-morbiditiesmentioning
confidence: 99%
“…The distal RYGB used in this study had a short common channel (distance from the entero-entero anastomoses to the ileocecal valve). We have previously shown that this variant of distal RYGB was associated with a higher prevalence of secondary hyperparathyroidism than standard RYGB [18]. To our knowledge, the effects of distal RYGB on bone turnover markers have not been reported.…”
Section: Introductionmentioning
confidence: 87%
“…Glucagon-like peptide 1 (GLP-1) and peptide tyrosine tyrosine (PYY) have been shown to have direct effects on bone metabolism, where GLP-1 has an insulin-independent anabolic effect on bone, and PYY direct effects inhibiting osteoblasts [9]. Distal gastric bypass leads to lower glucose, HbA1c, and LDL cholesterol despite similar weight loss, potentially indicating different effects on bile acids or gut hormones [18], but further studies are needed to investigate this.…”
Section: Possible Mechanisms and Explanationsmentioning
confidence: 99%
“…Many studiesconcur that the CL length and AL length do not affect the amount of potential weight loss that a patient can achieve [25][26][27][28] though Tran et al [29] has suggested the use of a distal bypass is an effective revision for a failed loss of weight on a standard bypass. There is certainly a range of results on whether proximal or distal bypasses have more pronounced effects on the metabolic and endocrine systems as reported by Risstad et al [9] and Ramos et al [30] Distal bypasses may also be related to increased rates of complication.…”
Section: Authors' Contributionsmentioning
confidence: 95%